Breast Cancer prevention and control programs in Malaysia - Dahlui, M.; Ramli, S.; Bulgiba, A.M. (2011)
Breast cancer is the most common cancer in Malaysian females. The National Cancer Registry in 2003 and 2006 reported that the age standardized incidence of breast cancer was 46.2 and 39.3 per 100,000 populations, respectively. With the cumulative risk at 5.0; a woman in Malaysia had a 1 in 20 chance of developing breast cancer in her lifetime. The incidence of cancer in general, and for breast cancer specifically was highest in the Chinese, followed by Indians and Malays. Most of the patients with breast cancers presented at late stages (stage I: 15.45, stage II: 46.9, stage III: 22.2 and stage IV: 15.5). The Healthy Lifestyles Campaign which started in the early nineties had created awareness on breast cancer and after a decade the effort was enhanced with the Breast Health Awareness program to promote breast self examination (BSE) to all women, to perform annual clinical breast examination (CBE) on women above 40 and mammogram on women above 50. The National Health Morbidity Survey in 2006 showed that the prevalence rate of 70.35 by any of three methods of breast screening; 57.1 by BSE, 51.8 by CBE and 7.6 by mammogram. The current screening policy for breast cancer focuses on CBE whereby all women at the age of 20 years and above must undergo breast examination by trained health care providers every 3 years for age between 20-39 years, and annually for age 40 and above. Several breast cancer preventive programs had been developed by various ministries in Malaysia; among which are the RM50 subsidy for mammogram by the Ministry of Women, Family and Community Development and the SIPPS program (a call-recall system for women to do PAP smear and CBE) by the Ministry of Health. Measures to increase uptake of breast cancer screening and factors as to why women with breast cancer present late should be studied to assist in more development of policy on the prevention of breast cancer in Malaysia.